Consumers' perspective on product care: An exploratory study of motivators, ability factors, and triggers. (10th May 2018) - Ackermann, Laura; Mugge, Ruth; Schoormans, Jan
Abstract: Product care is defined as all activities initiated by the consumer that lead to the extension of a product's lifetime. This research contributes to the literature by taking a consumer's perspective on product care, which is essential to postpone product replacement. We used Fogg's behaviour model as a theoretical framework to understand consumers' motivation, ability and triggers related to product care. Based on this, 15 in-depth interviews were conducted to explore consumers' current product care behaviour. Our findings show that many consumers are generally motivated to take care of their products, for example because they appreciate the product's functionality or because they are generally keen to consume in a sustainable way. They even have the right knowledge and tools or are at least motivated to get them. What is often missing are triggers that push people to take care of their products. Triggers can increase consumers' motivation or ability, for example by giving necessary tools to the consumer or by a helpful service offer. We also give suggestions for the practical implementation of our findings to support companies interested in a shift towards the Circular Economy. Highlights: Product care are consumer activities by the consumer to extend a product's lifetime. Current product care behaviour differs strongly between consumers. Different motivators, ability factors and triggers are explored. Consumers are generally motivated and able to take care of their products.